D‐limonene nanoemulsion: lousicidal activity, stability, and effect on the cuticle of Columbicola columbae. Issue 1 (31st August 2022) - Gadelhaq, Sahar M.; Aboelhadid, Shawky M.; Abdel‐Baki, Abdel‐Azeem S.; Hassan, Khaled M.; Arafa, Waleed M.; Ibrahium, Samar M.; Al‐Quraishy, Saleh; Hassan, Ahmed O.; Abd El‐Kareem, Shams G.
Abstract: The current study was conducted to investigate the efficacy and stability of D‐limonene (DL) and its nanoemulsion (DLN) against pigeon feather lice ( Columbicola columbae ) and their mode of action. DL pure form and DLN were prepared and characterized freshly and after storage for 50 days. In vitro bioassay on live lice was conducted with different concentrations of DL, DLN, and deltamethrin (DM). The results revealed significant mortality rates in the DL‐, DLN‐, DM‐treated groups when compared with the control ( p < 0.05). The scanning electron micrographs of lice treated with DL and DLN revealed collapsed bodies with destruction in the cuticle of the mouthparts and damaged antennae. The 50 days stored DLN showed stability in their effectiveness when compared with the freshly prepared formulation. DL and DLN caused significant inhibition ( p ≤ 0.05 ) in acetylcholinesterase activity (AchE). Malondialdehyde level (MDA) was significantly increased while glutathione was significantly decreased in DL‐ and DLN‐treated lice. In conclusion, DL and DLN have significant lousicidal activities. DLN showed better stability than DL after storage for 50 days. In addition, the mode of action of DL may associate with its effect on the cuticle of the lice body, inhibition of AchE, and increasing oxidative stress in the treated lice. Abstract : DL and DLN forms are effective against pigeon lice. The body of treated louse was flaccid and destroyed legs and collapsed abdomen. The treated lice showed significant inhibition in acetylcholinesterase activity.